Web-Based Interactive Applications in Macapat Learning to Introduce Local Wisdom Values - Nabilunnuha, Mantaaba Zukhruf; Sunarto, Sunarto; Sinaga, Syahrul Syah (Catharsis, 2023)
Macapat is a literary form with musical elements that is gradually losing its prominence in modern times. The limited efforts to preserve Macapat in Javanese language education necessitate innovation to engage students in learning activities. The utilization of technology can offer an intriguing learning experience. To this end, web-based applications can be employed to develop educational media. The purpose of this study is to describe the implementation of web-based interactive media in learning macapat and introducing the value of local wisdom. The research was conducted at SD Negeri Burengan 2 Kediri, with the participation of Javanese language class teachers and 5th grade students as research subjects. The data collection techniques in this study included observation, interviews, and documentation. After collecting the data, the researchers analyzed it using the Miles and Huberman model, which includes three stages: data condensation, data display, and conclusion drawing/verification. To ensure the data's validity, the researchers utilized data triangulation techniques. The study's findings demonstrate that website-based interactive media can enhance learning experience through interactivity. Various website-based applications like Canva, Wheelofnames, Online-Stopwatch, and Wordwall can serve as learning media. Employing interactive media helps guide students' focus, allowing for the effective transmission of the inherent value of local wisdom found in macapat.